2016
DOI: 10.1007/978-3-319-33714-2_25
|View full text |Cite
|
Sign up to set email alerts
|

The Inversion of Motion of Bristle Bots: Analytical and Experimental Analysis

Abstract: Bristle bots are vibration-driven robots actuated by the motion of an internal oscillating mass. Vibrations are translated into directed locomotion due to the alternating friction resistance between robots' bristles and the substrate during oscillations. Bristle bots are, in general, unidirectional locomotion systems. In this paper we demonstrate that motion direction of vertically vibrated bristle systems can be controlled by tuning the frequency of their oscillatory actuation. We report theoretical and exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
(17 reference statements)
2
9
2
Order By: Relevance
“…This behaviour has been already revealed in a bristle-bot featured by flexible joints between the bristles and the substrate [20,21]. The one we present here possesses rigid bristles.…”
Section: Ii23 Bristle Padssupporting
confidence: 74%
“…This behaviour has been already revealed in a bristle-bot featured by flexible joints between the bristles and the substrate [20,21]. The one we present here possesses rigid bristles.…”
Section: Ii23 Bristle Padssupporting
confidence: 74%
“…The possibility of backward locomotion in bristlebots was first predicted in [6] using a wet friction model, and further theoretically analyzed in [7], and experimentally observed for a macro-scale bristlebot (with > 10 cm feature size) using an external shaker [1]. Our work reports on the theoretical analysis of the bidirectional motion using Coulomb dry friction model, similar to the model used in [11].…”
Section: Introductionmentioning
confidence: 84%
“…At the other extreme, consider the artificial case in which µ s = 0 and µ k > 0. This is essentially the friction model used by [1]. We saw in the previous section that the introduction of µ k results in the bifurcation of resonance frequencies, and the equilibrium points, one for when the leg is slipping forward and one for when the leg is slipping backwards.…”
Section: Friction Resonance and Dampingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bristle-bots have also been popular in the field of small robotic system design (either soft or rigid) due to vibration-driven characteristic and compactness. Cicconofri et al presented a bristle-bot that was made of a polymer material for the body and two paper legs and its modeling [14]. Studies from various perspectives have been reported; for instance, the group behavior of multiple bristle-bots [15], the design of a millimeter-scale bristle robot (body length less than 10 mm) [16], and so on.…”
Section: Introductionmentioning
confidence: 99%